A comparison of patterns of a avifauna community structure between forested and open area in Jambusan, Bau, Sarawak - Emylda, Anak Dino. (Universiti Malaysia Sarawak (UNIMAS), 2005)
A study of avifauna community structure was conducted in Jambusan, Bau, Sarawak for six days continuously from 7 August 2004 to 12 August 2004. The aim of the study is to compare the patterns of avian community structure (species diversity, capture rate, composition, and temporal patterns) between forested area and open area in Jambusan, Bau. Forested areas are described as areas with scattered trees and without any mark of agriculture activities. Open areas are described as areas in which plantation activities were conducted and areas whereby some parts of the site have been logged. A total of 20 mist-nets were deployed in each of the sampling site with 10 mist-nets in the forested area and another 10 mist-nets in the open area. A total of 94 birds comprising 31 species from 14 families were recorded in the area. The analysis of Shannon-Weiner Index, H' comparing the indices of the forested and open areas show no significant different between the two areas. Family Ploceidae contribute the highest relative abundance with 20 birds and the relative abundance of 21.3%. The most dominant species was mossy-nest swiftlet (Aerodramus salanganus) with 13 birds have been captured. In forested area, a total of 20 species from 11 families were recorded while 22 species from 13 families were recorded in open area. Eleven species and nine families were recorded in both forested and open areas. The overall capture rate for this study was 37 birds/tOOO nethours. Throughout the study period, birds were most captured during the morning and evening with 39 birds.